Erodibilidade e perdas por erosão de latossolo vermelho amarelo distrófico e areias quartzosas distróficas na região da Ibiapaba, Ceará - Távora, Maria Risalva Pinheiro (1984)
Soil, water, organic matter and nutrient losses under simulated rainfalls were evaluated on Distrophic Quartz Sands (Quartzipsaments) and on a Distrophic RedYellow Latosol (Typic Haplustox) from the pyxiographic region of Ibiapaba, Ceara State, Brazil, in order to verify their behavior and resistance to erosion at the stage of seed bed preparation. [...]